Thermostable DNA ligases from hyperthermophiles in biotechnology - Shi, Jingru; Oger, Philippe M.; Cao, Peng; Zhang, Likui (Frontiers in Microbiology, 2023)
DNA ligase is an important enzyme ubiquitous in all three kingdoms of life that can ligate DNA strands, thus playing essential roles in DNA replication, repair and recombination in vivo. In vitro, DNA ligase is also used in biotechnological applications requiring in DNA manipulation, including molecular cloning, mutation detection, DNA assembly, DNA sequencing, and other aspects. Thermophilic and thermostable enzymes from hyperthermophiles that thrive in the high-temperature (above 80°C) environments have provided an important pool of useful enzymes as biotechnological reagents. Similar to other organisms, each hyperthermophile harbors at least one DNA ligase. In this review, we summarize recent progress on structural and biochemical properties of thermostable DNA ligases from hyperthermophiles, focusing on similarities and differences between DNA ligases from hyperthermophilic bacteria and archaea, and between these thermostable DNA ligases and non-thermostable homologs. Additionally, altered thermostable DNA ligases are discussed. Possessing improved fidelity or thermostability compared to the wild-type enzymes, they could be potential DNA ligases for biotechnology in the future. Importantly, we also describe current applications of thermostable DNA ligases from hyperthermophiles in biotechnology.